Peran Ekonomi Kreatif Dalam Meningkatkan Pendapatan Di Zaman Kopi Sengon Jombang - Febby Indah Oktavia; Lailatus Sa'adah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The purpose of this study is to understand the creative economic cycle in order to increase earnings in Zaman Kopi Sengon Jombang. The term "creative economy" refers to a new theory of economics that combines information with creativity to use ideas, insights, and opinions from everyday human beings as production-related factors. Zaman Cop's contribution to the creative economy is the invention of the cup gelas, which has become a symbol of the botol. As a result of this study's findings, creative economy is doing well in its current state, which causes productivity to also experience growth, The results of the study show that the creative economy is doing well in the country as a whole because of this, and that's why the rate of pay growth has also been increasing. For example, in September, the rate of pay growth was Rp. 12.488.000, and in October, it was Rp. 14.121.000. This indicates that the rate of pay growth was greater than Rp.2.000.000, and that the following month saw a similar increase. Economi creative also has a role to play in the development of economic fundamentals, particularly in regard to advancing monetary, labor, and other fundamentals.